Happiness: Exploring Relationship with Empathic Sense, Altruistic Behaviour, Social Responsibility, and Interpersonal Relationship - Wea, Donatus; Janu Hamu, Fransiskus (MIMBAR PGSD Undiksha, 2023)
An unhealthy personality makes students vulnerable to depression due to a lack of happiness. This research aims to analyze the relationship between altruistic behavior, empathy, social responsibility, interpersonal relationships, and happiness. The types of research used are surveys, cross-sectional, and correlational studies. A total of 149 students were selected through random-stratified sampling from high school students. Students fill out research instruments via Google Forms. The data obtained were analyzed using multivariate analysis with Smart-PLS software. The research results show a significant relationship between altruistic behavior, empathy, social responsibility, and interpersonal relationships on happiness. Happy individuals demonstrate more cooperative behavior and are more satisfied as students. Thus, happiness is one of the essential positive feelings and is vital in explaining overall life satisfaction and the degree of enjoyable quality of life for each individual. Positive affect dominates more than negative affect. Students must have these shifting skills as prospective young intellectuals who, in the future, will become agents of social control and agents of social change.